A Review Of PDSA Method To Improve Productivity In Education Sector - Mohamad Rafaai, Zubaidi Faiesal; Majid, Nur Nadzira; Abdul Rasib, Amir Hamzah (IJSRET, 2018)
Productivity is well defined as the utilization of resource to produce desirable output. In the case of productivity in the educational sector, the output that is desire is that of how well the student manage to understand what has been thought throughout the study period. The purpose of this paper is to review on how well the current educational system perform in its productivity and its efficiency through applying PDSA method.